THE EFFECT OF COMBINATION OF BABY MASSAGE AND LULLABY MUSIC THERAPY ON BABY SLEEP QUALITY: CASE REPORT - Mutiara Romadhon; Wahyudi Mulyaningrat; Annas Sumeru (International Journal of Biomedical Nursing Review, 2025)
Introduction: Good sleep is an important need for infant growth, because during sleep the baby's brain growth reaches its peak. Babies who do not get enough sleep will have their immune system lowered so that they are susceptible to disease. In addition, growth hormones will be disrupted, so that the baby's growth will also be disrupted. Efforts that can be used to meet the need for sleep in infants have developed, one of which is by combining baby massage with lullaby music therapy. Purpose: This study aims to determine the effect of the combination of infant massage and music therapy on the quality of sleep on infants. Methods: The writing of this scientific paper uses a case study method. This case study uses a nursing process approach on 3 healthy infant clients aged 0-12 months but have mild sleep problems. Discussion: The results of the study showed that after the intervention, the infant became more active during the day, looked more restful to sleep, the baby was easier to sleep and the baby cried but not as long as before. All mothers admitted that there was a change in their child's sleep pattern. After the combination of infant massage and lullaby music therapy, it was found that all infants experienced an increase in sleep quality to no problems. Conclusion: The combination of baby massage and lullaby music therapy has an effect on improving the quality of infant sleep.